CACA Technical guidelines for holistic integrative management of cancer —— genetic testing - CACA –Committee of Cancer Genetic Diagnosis; Bing Wei; Jinliang Xing; Xiaoyan Zhou; Jie Ma; Nengtai Ouyang; Jinpu Yu; Jinyan Huang; Hongxue Meng; Dan Su; Hongle Li (Holistic Integrative Oncology)
Abstract Cancer management increasingly benefits from advances in genetic testing, offering new opportunities for prevention, diagnosis, and personalized treatment. This guideline, developed by the Committee of Cancer Genetic Diagnosis of the Chinese Anti-Cancer Association (CACA), provides a comprehensive framework for integrating genetic testing into a holistic approach to cancer care. Addressing key aspects of genetic testing—including patient selection, testing protocols, interpretation of genetic results, and integration into treatment plans—this document is designed to support clinicians in making informed decisions that align with each patient’s unique genetic profile and overall well-being. By emphasizing evidence-based practices and incorporating input from experts in oncology and genetics, these guidelines aim to optimize the effectiveness of genetic testing in cancer care, ultimately enhancing outcomes and quality of life for patients. Our approach promotes the use of genetic insights as a complement to integrative oncology, underscoring the potential of genetic testing to improve holistic management strategies across various cancer types.